PECULIARITIES OF THE BINARY TEMPORAL OPPOSITIONS IN ELECTION DISCOURSE - Bilyk, О. І.; Pyliachyk, N. Ye. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The research reveals the peculiarities of the binary temporal oppositions in the American election discourse. The temporal concepts that make up the binary oppositions “present :: past”, “present :: future”, “past :: future”are discussed.The analysis of the concepts PAST, PRESENT, FUTURE is accompanied by emphasizing the positive/negative aspects of the past, present and future, due to implementing various strategies in election discourse.